Sensitive detection of noradrenaline in human whole blood based on Au nanoparticles embedded vertically-ordered silica nanochannels modified pre-activated glassy carbon electrodes - Huang, Liyuan; Su, Ruobing; Xi, Fengna (Frontiers in Chemistry, 2023)
Sensitive determination of noradrenaline (NE), the pain-related neurotransmitters and hormone, in complex whole blood is of great significance. In this work, an electrochemical sensor was simply constructed on the pre-activated glassy carbon electrode (p-GCE) modified with vertically-ordered silica nanochannels thin film bearing amine groups (NH2-VMSF) and in-situ deposited Au nanoparticles (AuNPs). The simple and green electrochemical polarization was employed to pre-activate GCE to realize the stable binding of NH2-VMSF on the surface of electrode without the use of any adhesive layer. NH2-VMSF was conveniently and rapidly grown on p-GCE by electrochemical assisted self-assembly (EASA). With amine group as the anchor sites, AuNPs were in-situ electrochemically deposited on the nanochannels to improve the electrochemical signals of NE. Owing to signal amplification from gold nanoparticles, the fabricated AuNPs@NH2-VMSF/p-GCE sensor can achieve electrochemical detection of NE ranged from 50 nM to 2 M and from 2 M to 50 M with a low limit of detection (LOD) of 10 nM. The constructed sensor exhibited high selectivity and can be easily regenerated and reused. Owing to the anti-fouling ability of nanochannel array, direct electroanalysis of NE in human whole blood was also realized.